Capacity worth of energy storage systems for renewable power generation plants - Zhou, Qian. (2009)
This report is based on a Final Year Project (FYP) offered by the School of Electrical and Electronic Engineering (EEE). The objective is to develop computational tool which can be used to assess the economics of a hybrid renewable-energy storage system, and to control stored energy through power dispatch. Through analysis, it is intended the study will provide some useful information on the hybrid renewable energy-energy storage system (ESS) to be designed. This report begins with a literature review, followed by the development of a computational procedure to calculate the optimal dispatch power level and capacity size of the ESS. A method to forecast the hybrid renewable output power 24-hour ahead is proposed. The final outcome of the above computational approach is to allow the dispatch-able level of the power output and the corresponding capacity of the ESS to be determined. Some areas recommended for future works are also included.